2016
DOI: 10.1371/journal.pone.0167140
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Inequality of Chronic Non-Communicable Diseases in Bangladesh

Abstract: IntroductionChronic non-communicable diseases (NCDs) are a major public health challenge, and undermine social and economic development in much of the developing world, including Bangladesh. Epidemiologic evidence on the socioeconomic status (SES)-related pattern of NCDs remains limited in Bangladesh. This study assessed the relationship between three chronic NCDs and SES among the Bangladeshi population, paying particular attention to the differences between urban and rural areas.Materials and MethodData from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
85
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 32 publications
14
85
3
Order By: Relevance
“…The prevalence of overweight and obesity that we report in urban Bangladesh (37%) is double the previous report of 17% based on a hospital (icddr,b) population of adults (≥20 years of age) in 2011 [18]. We found the prevalence of overweight and obesity in the rural areas (17%) was also higher than the 10% reported in rural women of reproductive age in 2000–2004 [19], but was less than half the prevalence reported in a rural community (aged ≥20 years) in 2009 which indicated that ~18% were overweight and 26% were obese[20]. In part, the discrepancy is due to different cut-points used to define overweight and obesity, as well as differences in the age of the population studied.…”
Section: Discussioncontrasting
confidence: 60%
“…The prevalence of overweight and obesity that we report in urban Bangladesh (37%) is double the previous report of 17% based on a hospital (icddr,b) population of adults (≥20 years of age) in 2011 [18]. We found the prevalence of overweight and obesity in the rural areas (17%) was also higher than the 10% reported in rural women of reproductive age in 2000–2004 [19], but was less than half the prevalence reported in a rural community (aged ≥20 years) in 2009 which indicated that ~18% were overweight and 26% were obese[20]. In part, the discrepancy is due to different cut-points used to define overweight and obesity, as well as differences in the age of the population studied.…”
Section: Discussioncontrasting
confidence: 60%
“…Similar to other studies in LMICs [8,23,37,38], our findings indicate the presence of inequalities in hypertension disfavouring the poor population. The magnitude of the inequalities in our study (C: -0.08) is lower compared to that of Iran (C: -0.15) [23,38] and among rural residents in Bangladesh (C: -0.20) [23,38] despite an almost similar hypertension prevalence reflecting the varying levels of inequalities. However, our findings differ from the pro-poor inequality in high blood pressure reported in a study among women of reproductive age in sub-Saharan Africa [13].…”
Section: Discussionsupporting
confidence: 90%
“…As like as other developing country, Bangladesh is experiencing a rapid demographic and epidemiological transition [ 8 – 10 ]which has been associated with increases in overweight and obesity. In 2011, cross-sectional data indicated that the overall prevalence of overweight and obesity combined in women who had been or were married was 18%[ 11 ], approximately 1.5 times that reported in women aged 20 to 49 years of age in 2007[ 12 ].…”
Section: Introductionmentioning
confidence: 99%